SYSTEMATIC LITERATURE REVIEW: PENGARUH MODEL PEMBELAJARAN TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS - Eka Pratiwi, Vivied; Meiliasari, Meiliasari (LPPM Universitas Bina Bangsa, 2024)
The purpose of this research is to reanalyze the influence of the learning model in an effort to improve the ability to understand mathematical concepts. After that, the analysis results are combined and a conclusion about the overall problem is obtained. The method in this research is the Systematic Literature Review (SLR). This research seeks, observes, evaluates, and describes the available research based on relevant phenomena and specific research questions. The SLR method reviews and identifies journals according to the established procedures. Data collection comes from journals indexed by Sinta and Google Scholar over the past 6 years. The keywords for the search are